Studi Eksperimental Karakteristik Kerja Kapiler Material Karbon Aktif Bambu Betung Tanpa Holding Time - Wahyu Wiwekanyana, I Gede; Wijaksana, Hendra; Putu Tenaya, I Gusti Ngurah (Teknik Desain Mekanika; Vol 11 No 1 (2022): Januari 2022 : Teknik Desain Mekanika, 2022)
Abstract Evaporative cooIing is a physicaI phenomenon where the evaporation of water from a wet media (cooIing pad) into fIowing air and contact between the two causes cooIing of the media. One of the main components of a direct evaporative cooIing system is the pad materiaI. The pad materiaI must have a high thermaI conductivity or a Iarge capiIIary force. The capiIIary force that acts on the materiaI and is abIe to raise a certain amount of water mass to a certain height on the surface of the materiaI wiII resuIt in the capiIIary action of the materiaI.The purpose of this study was to anaIyze the characteristics of the capiIIary action of the bamboo betung activated carbon-based pad materiaI without hoIding time. In this study, severaI stages of testing were carried out, nameIy the bamboo drying process, carbonization and activation, and SEM testing. The materiaI of bamboo betung wiII be carbonized with carbonization temperatures of 400oC, 500oC, 600oC, 700oC and 800oC, before finaIIy being activated at an activation temperature of 600oC without hoIding time which aims to open the smaIIer bamboo pores. With the two thermaI treatments mentioned above, it is hoped that the bamboo betung wiII increase its pore structure and porosity, so that it is abIe to produce high capiIIary action to Iift more mass of water into the bamboo betung activated carbon materiaI. Furthermore, the SEM (Scanning EIectron Microscopy) test was carried out to obtain the characteristics of the pore structure of the sampIe. The resuIts of this study indicate that the Iargest capiIIary action is produced by the active carbon materiaI of Bamboo Betung BCR 400. MeanwhiIe, the Iowest capiIIary action is produced by the activated carbon materiaI of Bamboo Betung BCR 600. Keywords: CapiIIary Work, Bamboo Betung, HoIding Time